Kelembagaan Lokal dalam Pengelolaan Sumber Daya Alam Hutan Mangrove : (Studi Kasus di Pantai Litianak Desa Holulai, Kec Loaholu, Kab Rote Ndao) - Yemima Ingamita; Alfred Omri Ena Mau; Syahrin Badrin Kamahi (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
The mangrove forest at Litianak Beach, Holulai Village, Loaholu Subdistrict, Rote Ndao Regency, is a coastal ecosystem with high ecological and economic value. However, this area faces various challenges, including land conversion, overexploitation, and low community awareness of the importance of mangrove ecosystem conservation. This study aims to analyze the role of local institutions in the management of mangrove forest natural resources using a qualitative approach through field research methods. The research focuses on four key institutional aspects: context, structure, behavior, and performance.The findings indicate that mangrove management in Litianak Beach involves synergy between the village government, Village-Owned Enterprises (BUMDes), the Welaleo customary group, and the local community. This institutional structure has proven effective in raising public awareness and reducing illegal logging activities through customary regulations such as Papadak. However, challenges such as economic pressures, tourist waste, and uncertain access to mangrove resources remain obstacles that need to be addressed. The performance of the management shows positive results, marked by increasing community participation in conservation efforts and the development of sustainable mangrove resource utilization.This study highlights the importance of a participatory and culturally rooted local institutional approach in sustaining the mangrove ecosystem while improving the welfare of coastal communities. Strengthening institutional capacity and providing intensive environmental education are essential to ensure more effective and sustainable mangrove management in the future.